(3ehShYI CbhGd dG JeMhgG GdCjGe (B/s - (3YHO QHg, YHO GdQRGbs ((3YeGf(B-(3GdCQOf (B:s (3OGQ GdacQ ddWHGYI h GdfTQ h GdJhRjY ,s, 1995)
(3gPG GdcJjH jfJej Gdi GdTYH agh jYHQ Yf TNUjI GdeLJeY GcKQ eeG jYHQ Yf TNUjI GdaQO Gh GdcGJH h jMJhj Ydi eKjQ ef GdGeKGd GdTYHjI HeG dgG ef NUGFU h SeGJ JejRgG Yf ShGgG ef GfRGY GdJQGK GdGfSGfj cGdGjLGR aj cdeGJgG h YHGQGJgG GdbdjdI GdehMjI dOdGdI NGUI h GdMceI h GdUQGMI h GdNdhO h GbhGd GdMcGe YQHG h GaQGfLG h adGSaI ef GdTQb h GdZH JJVef eLGdGJ GdMjGIs
Keywords: (3CbhGds; (3GdCOHs; (3ehShYIs